2018
DOI: 10.3390/ijerph15102309
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction, Interpersonal Relationships, and Learning Influence Withdrawal from School: A Study among Junior High School Students in Japan

Abstract: School absenteeism, particularly among junior high school students, has increased annually in Japan. This study demonstrates the relationship between subjective adjustment to school life and students’ absenteeism. Data were collected from 17,378 junior high school students in Japan. A longitudinal design was used for the study. Teachers were asked to distribute the Adaptation Scale for School Environments on Six Spheres (ASSESS) questionnaire to junior high school students and ask the students to fill out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This can be due to such children feeling that school and school friendships are not a safe environment. In Indonesian culture, negative stigma from one's environment is considered to be very shameful (Budirahayu et al, 2018 ), so the relationship between friends is very important, in some cases, even greater than other needs (Lubis et al, 2019 ). An Indonesian study by Waliyanti and Kamilah ( 2019 ) found that teenagers can have high tolerances for acts of violence committed against their friends because bullies tend to dominate peer groups, causing teenagers to fear that they themselves will be bullied if they speak up.…”
Section: Discussionmentioning
confidence: 99%
“…This can be due to such children feeling that school and school friendships are not a safe environment. In Indonesian culture, negative stigma from one's environment is considered to be very shameful (Budirahayu et al, 2018 ), so the relationship between friends is very important, in some cases, even greater than other needs (Lubis et al, 2019 ). An Indonesian study by Waliyanti and Kamilah ( 2019 ) found that teenagers can have high tolerances for acts of violence committed against their friends because bullies tend to dominate peer groups, causing teenagers to fear that they themselves will be bullied if they speak up.…”
Section: Discussionmentioning
confidence: 99%
“…The ASSESS evaluates children's subjective feelings of adaptation to the school environment (Inoue et al, 2018; Kurihara & Inoue, 2010). It contains 34 items that are each rated on a 5‐point Likert scale, ranging from 1 ( not at all true ) to 5 ( extremely true ).…”
Section: Methodsmentioning
confidence: 99%
“…These include avoidance of the distress associated with typical school-related activities, such as traveling in the bus, entering the school, and changing classrooms. Other youngsters evade school because of social or evaluative reasons: they experience difficulties when interacting with peers and/or fear performance situations, such as exams, oral presentations, and sports (see also Inoue et al, 2018 ). Besides these negative motives, there may also be positive incentives that make it more appealing to be at another place than school.…”
Section: Related Conceptsmentioning
confidence: 99%